The Northern Territory Press. Issue 1 (February 2014) - Hamilton, Stephen; Carment, David
The history of print media in the Northern Territory is one of parish pumps and media moguls, Cold War tensions and human rights crusades. Locally printed and published newspapers have been pivotal to the development of a Northern Territory identity and the cultivation of the Territory's sense of difference from the rest of Australia. From the earliest newspapers – part news-sheet, part government gazette – to the colourful online edition of the NT News, the Territory has been defined by its press and has in turn defined it, in response to its remoteness and to its increasing non-Indigenous population. This article provides a brief overview of the Northern Territory press, the history of which remains poorly documented.